Revisiting Early Islamic Trade Networks in Nusantara: A Comparative Study of Three Historical Sources - Muhammad Faiz; Muhammad Hasbi Abror BM; Arwansyah Kirin (Universitas Darussalam Gontor, 2026)
The theory of the arrival of Islam in Indonesia cannot be separated from the historical evidence discovered over the past century. New historical evidence can strengthen one theory and weaken another, but more importantly, how this scattered evidence can be connected within a coherent narrative framework. This article seeks to clarify the existing historical evidence within the oldest scope as part of authentic historical writing, with a particular focus on the relationship between three primary sources that have often been analyzed separately. The method used is a historical research method that includes heuristics, verification, interpretation, and historiography. The primary sources used in the form of a manuscript of Al-Masalik wa Al-Mamalik by Ibn Khurdadhbih, thetombstone of Abu Kamil from Phan Rang, southern Champa, and the tombstone of Fatimah binti Maimun from Leran, Gresik. The results of the study reveal the Islamic trade network contained in the oldest source and its relationship with the two primary sources in the form of tombstones, all of which show a similar pattern of trade routes connecting the Islamic world with China through the Nusantara. This network is the Malay-Javanese-Champa-Chinese trading network which has been operating since the IX century AD and has left archaeological evidence that can still be seen today.